Modelling and usability evaluation of collaborative awareness in synchronous distributed groupware for home modification - Lim, Tek Yong (Universiti Malaysia Sarawak (UNIMAS), 2008)
Three main problem in this thesis. First, the need for a theoretical framework to guide development of a synchronous distributed groupware. Second, the need to evaluate the usability of the groupware using standard measurement metrics. Third, the need to develop collaborative tasks that enabled measurement of collaborative awareness.